2012
DOI: 10.1007/s12264-012-1216-8
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of δ-opioid receptor phosphorylation at Threonine 161 attenuates morphine tolerance in rats with CFA-induced inflammatory hypersensitivity

Abstract: Objective Our previous study identified Threonine , located in the second intracellular loop of the δ-opioid receptor (DOR), as the only consensus phosphorylation site for cyclin-dependent kinase 5 (Cdk5). The aim of this study was to assess the function of DOR phosphorylation by Cdk5 in complete Freund's adjuvant (CFA)-induced inflammatory pain and morphine tolerance. Methods Dorsal root ganglion (DRG) neurons of rats with CFA-induced inflammatory pain were acutely dissociated and the biotinylation method was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Its substitution by Ala or the inhibition of Cdk5 reduces basal DOPr phosphorylation status both in immortalized cell lines and in DRG neurons . As detailed in section V.A, in its phosphorylated state, Thr161 promoted DOPr expression at the membrane and its heterodimerization with MOPrs Chen et al, 2012).…”
Section: Regulation Of D-opioid Receptor Signalingmentioning
confidence: 87%
See 1 more Smart Citation
“…Its substitution by Ala or the inhibition of Cdk5 reduces basal DOPr phosphorylation status both in immortalized cell lines and in DRG neurons . As detailed in section V.A, in its phosphorylated state, Thr161 promoted DOPr expression at the membrane and its heterodimerization with MOPrs Chen et al, 2012).…”
Section: Regulation Of D-opioid Receptor Signalingmentioning
confidence: 87%
“…Finally, DOPrs are also substrates for Cdk5 Chen et al, 2012). Cdk5 is a prolinedirected serine/threonine kinase that requires proline in the +1 position and displays a preference for substrates bearing a basic residue in the +3 position relative to the substrate residue (Songyang et al, 1996).…”
Section: Regulation Of D-opioid Receptor Signalingmentioning
confidence: 99%
“…They also discuss the controversy in the field [14] . The functional interactions of the µ-and δ-opioid receptors are further supported in the paper from Chen et al, reporting that the disruption of phosphorylation of the δ-opioid receptor at a specific site (Threonine 161) can attenuate morphine tolerance in the context of inflammatory pain [15] .…”
mentioning
confidence: 86%
“…Ten laboratories from China and the USA have contributed 11 papers to this special issue: 5 reviews and 6 full research articles [5][6][7][8][9][10][11][12][13][14][15] . This special issue aims to cover several areas of research in pain and itch, from peripheral to central mechanisms, and also from neuronal to glial mechanisms.…”
mentioning
confidence: 99%
“…Early studies showed that blockage of δ‐opioid receptors enhanced morphine analgesia, and reduced analgesic tolerance (Abdelhamid et al ., ; Schiller et al ., 1999a,b; Schiller, ). Further studies revealed that morphine tolerance can be reduced by intrathecal application of the antisense oligodeoxynucleotide of the δ‐opioid receptor gene ( Oprd1 ), deleting either Oprd1 or the preproenkephalin gene ( Penk1 ), preventing δ‐opioid receptor phosphorylation or deleting Tac1 , which reduces the transport of δ‐opioid receptors to the spinal dorsal horn via LDCVs (Standifer et al ., ; Zhu et al ., ; Nitsche et al ., ; Guan et al ., ; Xie et al ., ; Chen et al ., ).…”
Section: Role Of Opioid Receptor Interaction In Morphine Antinociceptmentioning
confidence: 99%